2019
DOI: 10.1155/2019/5383010
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Identified Long Noncoding RNA in Diabetic Nephropathy

Abstract: Diabetes mellitus is the leading chronic disease in the world, and diabetic nephropathy (DN) as one of its complications could increase the mortality. The development of DN is associated to abnormal hemodynamic factors like cytokine networks and the intervention of metabolic risk factors like blood pressure, blood glucose, and blood lipid. However, the pathogenesis of DN is still poorly understood. Although glucose-lowering drugs and insulins have significant effects on blood glucose, the fluctuation of blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 82 publications
0
57
0
Order By: Relevance
“…DN is a lethiferous end‐stage complication of diabetes 27,28 . LncRNAs can effectively participate in the pathophysiological process of DN 29,30 . For instance, we found that lncRNA 150Rik can promote proliferation of mesangial cells via regulating miR‐451 and p38 MAPK pathway in DN 31 .…”
Section: Discussionmentioning
confidence: 84%
“…DN is a lethiferous end‐stage complication of diabetes 27,28 . LncRNAs can effectively participate in the pathophysiological process of DN 29,30 . For instance, we found that lncRNA 150Rik can promote proliferation of mesangial cells via regulating miR‐451 and p38 MAPK pathway in DN 31 .…”
Section: Discussionmentioning
confidence: 84%
“…Growing evidence suggests that a group of lncRNAs regulate glucose homeostasis and pathogenesis of DM, especially in diabetic complications [91][92][93]. These lncRNAs include Risa, HOTAIR, and Meg3 [94].…”
Section: Regulation Of Insulin/igf Signaling By Lncrna In Dm and Cancermentioning
confidence: 99%
“…Notably, recent studies suggest a close relationship between lncRNAs and DN. A number of lncRNAs have been identified to contribute to the pathogenesis and progression of DN [9]. For example, lncRNA TUG1 has been reported to alleviate extracellular matrix accumulation via downregulating microRNA-377 (miR-377) in a mouse model of DN [10] and regulate the mitochondria function in podocytes [11].…”
Section: Introductionmentioning
confidence: 99%